(untitled) (Productivity, 2020)
This study aims to determine the effect of promotion on the Daihatsu Sigra car purchase decision at PT. Astra Daihatsu Malalayang. This research method uses a quantitative research approach. This research was conducted on Daihatsu Sigra consumers with a sample of 93 respondents. The result of R between the two variables is 0.565, meaning the relationship between promotion and purchasing decisions is moderate. Then R square (determinant coefficient) of 31.9%. This shows that the decision to buy Daihatsu Sigra car at PT. Astra Daihatsu Malalayang, 31.9% was influenced by promotion, while the other 68.1% was determined by other factors not examined in this study. Then the influence is interpreted that the promotion is one factor that is sufficient to influence the decision of buying a Daihatsu Sigra car. In this case that the promotion carried out by PT. Astra Daihatsu Malalayang can satisfy consumers, because promotion is a way to introduce existing products at PT. Astra Daihatsu Malalayang especially Daihatsu Sigra cars.